Options for the eradication of bovine leukemia virus infection in dairy cattle - Y. P. Smirnov; I. L. Suvorova; N. A. Gryazeva (Аграрная наука Евро-Северо-Востока)
The article presents options of the control of bovine leukemia virus infection in dairy cattle depending on the character of the epizootic situation and economic opportunities of agricultural enterprises. When the within-herd BLV prevalence in breeding stock ranges from 2.5% to 10% it is recommended to slaughter all infected animals and to test all seronegative animals with 1-3 month intervals which should be slaughtered until the results of last two successive serological examinations are negative. When the within-herd BLV prevalence ranged from 10 to 30-40% all infected animals should be isolated by grouping them in separate groups; sick animals should be culled and slaughtered. Seronegative animals were tested serologically every three months; when the BLV prevalence decreases to 1% serological testing was carried out monthly. Seropositive cows should be replaced by seronegative heifers. The herd can achieve BLV free status in 4-4.5 years. When the within-herd BLV prevalence was more than 40% all animals was tested haematologically every 6 months, seropositive heifers were selected for fattening. Seronegative heifers were used for replacement of seropositive animals in large farms. Seronegative cows were isolated from seroreagents by grouping them in a separated area of the same barn. The herd can be given official BLV-free status in 1-1.5 years if testing intervals in 1-3 months are respected. When economic opportunities allowed it was recommended to eliminate the livestock and to replace it by animals imported from BLV-free farms. The effectiveness of eradication programme can be improved when using highly sensitive methods of diagnostics of leukemia polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) and biologically active substances with immunomodulating activity (T- and B-activins, Ligfol, phosprenil and others).